Transparency in global agribusiness: Transforming Brazil's soybean supply chain based on companies' accountability - Gabriel Medina; Karim Thomé (Logistics, 2021)
Background: Although agri-food supply chains have become fundamental for food security throughout the world, some are associated with negative environmental and socioeconomic impacts. This study explores the possibilities of transforming the governance in Brazil's soybean supply chain based on stakeholders' accountability. Methods: We used secondary data from companies' reports and statistical yearbooks to identify key stakeholders in the soybean supply chain as well as to explore trade-offs between reducing farming expansion into new agricultural frontiers and increasing investments in agro-industrial sectors. Results: The results reveal that at the global level, multinational corporations along with domestic groups should be held accountable for improving the governance of the soybean supply chain in Brazil since foreign multinationals control 65.4% of it. At the domestic level, losses in Brazil's farming sector can either be offset by an 11% or 5.2% market share increase in the trading segment or in the whole supply chain, respectively, since Brazilian groups control 93.4% of the farming sector but only 7.1% of the agro-industrial sectors. Conclusions: Global accountability and domestic trade-offs are fundamental for transforming governance in global agri-food supply chains. They serve as a means for overcoming the current strategy of expansion into new farming frontiers.
Keywords: 650; business evolution; corporate environmental management; environmental; food supply chains transformation; responses to environmental issues; social and governance values (ESG); stakeholder accountability